Aluminum/Nitrogen Cycles and an Open Cage with Al–H and N–H Functions. Issue 20 (9th October 2017) - Veith, Michael; Walgenbach, Andreas; Huch, Volker; Kohlmann, Holger
Abstract : The cyclic tert ‐butyl‐amino alane dimer [ t Bu–N(H)AlH2 ]2 (1 ) was obtained from reaction between alane with tert ‐butylamine and its boranate derivative [ t Bu–N(H)–Al(BH4 )2 )]2 (2 ) subsequently from1 by hydride/chloride exchange using PbCl2 followed by reaction with LiBH4 . Both compounds form four‐membered Al2 N2 cycles with typical Al–N bond lengths of 1.940(5) Å (1 ) and 1.945(5) Å (2 ) as found from X‐ray diffraction analysis. The tert ‐butyl substituents at the nitrogen atoms may be situated at the same side of the ring ( cis ) or at opposite sides ( trans ). For compound1 both isomers are present in solution, showing particular temperature dependent NMR shifts. In the solid both compounds1 and2 adopt the trans arrangement. When1 is reacted with PbCl2 in half of the molarity ratio used for2, surprisingly the novel compound3, a zwitterion, can be obtained: [( t Bu–N)(Al–H)3 ( t Bu–N(H))3 Cl((H)N– t Bu)3 (Al–H)2 (Al–Cl)(N– t Bu)] + [( t Bu–N)( t Bu–N(H))(AlCl2 )2 ] – . X‐ray structure analysis reveals that the anion is made of a tert ‐butyl amino aluminum dichloride dimer (central Al2 N2 ring) with one of the two nitrogen atoms being deprotonated. The cationic counterpart consists of three entities: (i) There is a first seco‐norcubane like Al3 N4 basket with tert‐butyl groups at the nitrogen atoms, two hydride and one chloride ligand at the aluminum atoms and three hydrogen atoms on the open side of the basket, all pointing in the same direction; (ii) There is a second similar Al3 N4 basket with the same substituent pattern except that all aluminum atoms have exclusively hydrogen ligands; (iii) Both baskets coordinate a central chloride through the six protons at the open nitrogen face of the baskets in such a way that the chloride lies in the center of a H6 trigonal anti‐prism [mean H–Cl–H = 56.1(9)°]. As each of the open cages has a positive charge the overall charge by combination with the chloride adds to +1. The structure of the cationic part of3 is unprecedented in AlN polycycles. Abstract :